2012
DOI: 10.1111/j.1476-5381.2011.01819.x
|View full text |Cite
|
Sign up to set email alerts
|

Lost in translation: preclinical studies on 3,4‐methylenedioxymethamphetamine provide information on mechanisms of action, but do not allow accurate prediction of adverse events in humans

Abstract: Methylenedioxymethamphetamine (MDMA) induces both acute adverse effects and long-term neurotoxic loss of brain 5-HT neurones in laboratory animals. However, when choosing doses, most preclinical studies have paid little attention to the pharmacokinetics of the drug in humans or animals. The recreational use of MDMA and current clinical investigations of the drug for therapeutic purposes demand better translational pharmacology to allow accurate risk assessment of its ability to induce adverse events. Recent ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
68
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(70 citation statements)
references
References 111 publications
0
68
1
1
Order By: Relevance
“…In summary, contrary to what has been recently suggested (Green et al, 2012), alterations or differences in MDMA metabolism do not account for either the neuroprotective effect of hypothermia or the different profile of MDMA neurotoxicity observed in mice and rats. Additional studies will, therefore, be needed to understand the basis for both of these phenomena.…”
Section: Tablecontrasting
confidence: 45%
See 2 more Smart Citations
“…In summary, contrary to what has been recently suggested (Green et al, 2012), alterations or differences in MDMA metabolism do not account for either the neuroprotective effect of hypothermia or the different profile of MDMA neurotoxicity observed in mice and rats. Additional studies will, therefore, be needed to understand the basis for both of these phenomena.…”
Section: Tablecontrasting
confidence: 45%
“…In both rats and mice, hypothermia attenuates MDMA neurotoxicity, whereas hyperthermia exacerbates MDMA neurotoxicity O'Callaghan, 1994, 1995;Malberg and Seiden, 1998;O'Shea et al, 2006;Goni-Allo et al, 2008). It has been hypothesized that differences in MDMA metabolism underlie MDMA's different neurotoxic profile in rats and mice (Lim et al, 1992;de la Torre and Farre, 2004;Green et al, 2012). Similarly, it has been suggested that the neuroprotective effects of hypothermia on MDMA neurotoxicity are secondary to temperature influences on MDMA metabolism (Goni-Allo et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Green et al (2009Green et al ( , 2012 compared literature values for plasma MDMA concentrations following highdose MDMA administration in rats (i.e., 5-20 mg/kg via i.p., s.c., or po routes) to those produced by low-dose administration in humans (i.e., 0.5-2 mg/kg po). From this comparison, the authors concluded that MDMA doses in rats must be 4-fold higher than human doses to achieve similar peak plasma MDMA concentrations and that MDMA pharmacokinetics are linear in rats.…”
Section: Discussionmentioning
confidence: 99%
“…MDMA has a wide spectrum of psychological and physiological effects, including weak rewarding and addicting potentials in animals and humans (Green et al 2003;Reinhard and Wolffgramm 2006). Alongside a controversial discussion of the beneficial versus harmful potential of MDMA (Green et al 2012;Parrott 2012), the effects of the drug continue to be investigated, e.g. on cognition (Mithoefer et al 2013;Nelson et al 2013) and the motor system (Baumann et al 2008).…”
Section: Introductionmentioning
confidence: 98%